Optimizing Instruction in Air Conditioning Technology: A VAK Learning Styles Perspective in Malaysia TVET - Hashim, Suhaizal; Mohd Zamzuri, Ahmad Aizzat Arif; Abdul Rahman, Khairul Anuar; Zulkifli, Nurul Nadwa; Zulkifli, Nurul Nadwa (Online Journal for TVET Practitioners, 2025)
Technical and Vocational Education and Training (TVET) refers to technology-focused education in Malaysia. TVET emphasizes skill-based education programs to meet industrial needs, with air conditioning technology being a prominent area of focus within TVET. Air conditioning is a technology that controls the temperature and humidity of the air in a particular area. Aviation maintenance students at a TVET university must study air conditioning and cabin pressure. This topic is essential for ensuring the safety and comfort of passengers while traveling by air. Some methods of transmitting knowledge about inaccessible parts of the aircraft are ineffective, resulting in a lack of engagement and comprehension among students. The study examines the insufficient teaching resources for Module 11 on turbine airplane aerodynamics, structure, and systems, particularly focusing on the air conditioning and cabin pressure subtopic at a Malaysian polytechnic. This study employs the product design and development research (DDR) technique. The researcher concentrated on creating an instructional teaching board for the educational process through a quantitative approach. The concept is rooted in Visual, Auditory, and Kinesthetic (VAK) learning styles, aiming to enhance learning experiences for students and teachers. The research adheres to the ADDIE instructional design technique, progressing through analysis, design, development, implementation, and evaluation phases. Three experts evaluated a questionnaire based on specific predetermined criteria for this research. They all concurred that the teaching board paradigm is effective as a teaching tool. The aircraft air conditioning basic cycle model is anticipated to significantly enhance the teaching and learning process.